2004
DOI: 10.1159/000079943
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Cortisol, a Biological Marker of Stress, Is Positively Associated with 24-Hour Systolic Blood Pressure in Patients with Acute Ischaemic Stroke

Abstract: Background/Aim: The cause of elevated blood pressure (BP) in acute stroke is unknown. Stress is often suggested as a main contributing factor. We aimed to investigate the relationship between BP and stress in patients with acute stroke. Methods: 58 patients with clinical symptoms of stroke were recruited prospectively after exclusion of haemorrhage by CT scan within 14 h and 15 min (mean) after symptom onset (range 2 h and 45 min–23 h and 40 min). The mean age of the patients was 66 years (range 39–86 years), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 54 publications
3
30
0
1
Order By: Relevance
“…As such, the findings indicate that salivary amylase can be useful as a novel diagnostic biomarker for AMI 21) . Ahmed et al 22) conducted a study on 58 adult ischemic stroke patients within 24 hours of onset, monitoring BP and salivary cortisol for 24 hours. A positive correlation was observed between salivary cortisol and 24-hour mean systolic BP, as well as nighttime BP, indicating that stress and elevated BP are associated 22) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, the findings indicate that salivary amylase can be useful as a novel diagnostic biomarker for AMI 21) . Ahmed et al 22) conducted a study on 58 adult ischemic stroke patients within 24 hours of onset, monitoring BP and salivary cortisol for 24 hours. A positive correlation was observed between salivary cortisol and 24-hour mean systolic BP, as well as nighttime BP, indicating that stress and elevated BP are associated 22) .…”
Section: Discussionmentioning
confidence: 99%
“…Ahmed et al 22) conducted a study on 58 adult ischemic stroke patients within 24 hours of onset, monitoring BP and salivary cortisol for 24 hours. A positive correlation was observed between salivary cortisol and 24-hour mean systolic BP, as well as nighttime BP, indicating that stress and elevated BP are associated 22) . The present study showed increased salivary cortisol in ischemic stroke patients, as was seen in the Ahmed study, but did not indicate any correlation with severity or infarct volume.…”
Section: Discussionmentioning
confidence: 99%
“…Poststroke high blood pressure has been related to both urinary catecholamines [10] and salivary cortisol [11], suggesting that a neuroendocrine stress response explains the poststroke blood pressure changes. The processes leading to activation of this response are not clear, and may include psychological stress including a white-coat effect as suggested by Christensen et al [7].…”
Section: Discussionmentioning
confidence: 99%
“…This is also the case in neurological conditions. Association of GCs with stroke evolution and prognosis has for instance been highlighted in clinical terms, since cortisol levels were found high during the first post-stroke week and such concentrations were associated with higher prevalence of systolic blood hypertension and night-time blood hypertension 24-hours after stroke (Ahmed et al, 2004), and with increased dependency, delirium incidences, depression and mortality rates in post-stroke patients (though these conclusions are not necessarily independent of stroke severity and thus GC levels cannot be used as independent prognostic markers) (Barugh et al, 2014).…”
Section: Inconsistencies In Our Understanding Of Gc Therapeutics In Nmentioning
confidence: 99%